KONSTRUKSI PEMAHAMAN KONSEP BANGUN DATAR MELALUI GAME-BASED LEARNING PADA SISWA KELAS V SDN 1 PATALAN - Novia Wahyu Ika Wijianti; Aqidatul Munfariqoh; Anna Mariyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the experiences of fifth-grade students in constructing their understanding of flat shapes (bangun datar) through Game-Based Learning at SDN 1 Patalan, and to identify the factors that influence this process. A qualitative approach with a phenomenological method was employed. The research subject was the fifth-grade teacher as the primary informant. Data collection techniques included in-depth interviews, participatory observation, and documentation. The results indicate that fifth-grade students have diverse learning characteristics, and the teacher utilized concrete objects in the students' environment to explain flat shape concepts. The implementation of Game-Based Learning using visual media and Interactive Flat Panel (IFP) proved effective in increasing students' enthusiasm, confidence, and interest in flat shapes. Student understanding developed through repeated practice, enabling them to differentiate similar-shaped figures, understand the concepts of vertices, fold symmetry, rotational symmetry, and diagonals, and explain conclusions in their own words. The main obstacle was the gap in students' ability to use information technology. These findings confirm that Game-Based Learning can be an effective and meaningful alternative mathematics learning strategy in elementary schools.